Spontaneous remission of acute myeloid leukemia. Issue 6 (June 2015) - Rashidi, Armin; Fisher, Stephen I.
Abstract Spontaneous remission (SR) of acute myeloid leukemia (AML) is rare. We collected all 46 reported cases of AML with SR. Fever occurred in 91.3% of cases before remission, which was largely due to pneumonia (54.5%) and bacteremia (24.2%). Pneumonia and bacteremia were significantly more common among those who achieved complete remission (CR) compared to those who achieved only a partial remission (p = 0.032). Although 88.6% of remissions were CR, the median duration of remission was only 5 months. Eight cases did not relapse during the follow-up period. The mechanism of SR in AML likely involves the stimulatory effect of systemic febrile infection on the immune system. Immediate treatment of infections and fever may contribute to the rarity of SR in AML. The results of this review improve our understanding of the important role of the immune system in countermanding AML and may provide new ideas for immunotherapy.